1995
DOI: 10.1523/jneurosci.15-04-03138.1995
|View full text |Cite
|
Sign up to set email alerts
|

Recordings from slices indicate that octopus cells of the cochlear nucleus detect coincident firing of auditory nerve fibers with temporal precision

Abstract: Acoustic information in auditory nerve discharges is integrated in the cochlear nuclei, and ascends through several parallel pathways to higher centers. Octopus cells of the posteroventral cochlear nucleus form a pathway known to carry information in the timing of action potentials. Octopus cells have dendrites oriented to receive converging input from many auditory nerve fibers. In all 34 intracellular recordings from anatomically identified octopus cells in slices, shocks to the auditory nerve evoked brief, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

41
292
1

Year Published

1997
1997
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(334 citation statements)
references
References 64 publications
41
292
1
Order By: Relevance
“…These neurons require the summation of many synaptic inputs within a period of 1 ms to fire and thus detect coincident firing among their inputs [37]. In requiring the summation of many small inputs to produce a brief but robust synaptic response, the temporal jitter in the timing of individual auditory nerve inputs is lost in the firing of octopus cells.…”
Section: Temporal Precision In Responses Of the Cochlear Nuclei And Nmentioning
confidence: 99%
“…These neurons require the summation of many synaptic inputs within a period of 1 ms to fire and thus detect coincident firing among their inputs [37]. In requiring the summation of many small inputs to produce a brief but robust synaptic response, the temporal jitter in the timing of individual auditory nerve inputs is lost in the firing of octopus cells.…”
Section: Temporal Precision In Responses Of the Cochlear Nuclei And Nmentioning
confidence: 99%
“…1) and terminate in the cochlear nucleus (Lorente de No 1933;Fekete et al 1984;Brown et al 1988a). Type I fibers have an excitatory influence on their postsynaptic targets, leading to discharge of cochlear-nucleus neurons (Pfeiffer 1966;Golding et al 1995;Kopp-Scheinpflug et al 2002). Type I targets in the cochlear nucleus are a variety of types of neurons (Brawer and Morest 1975;Rouiller et al 1986), which have been classified by their morphology using different stains (Osen 1969;Brawer et al 1974).…”
Section: Introductionmentioning
confidence: 99%
“…Octopus cells have been assumed to act as coincidence detectors (e.g., Oertel et al, 2000) due to the large number of high-spontaneous rate AN fibers (Liberman, 1993) providing across-frequency excitatory AN input and due to their rapid membrane time constant (<200 µs) (Golding et al 1995(Golding et al , 1999. However, as was already shown by Kalluri and Delgutte (2003a), coincidence detection itself is not sufficient to simulate the ideal onset responses to pure tones observed in octopus cells.…”
Section: Change Detection Versus Stimulus Integrationmentioning
confidence: 99%
“…The general ability of these cells to entrain to periodic stimuli has led to the assumption that octopus cells may play an important role in the processing of amplitude modulation and pitch information (Golding et al, 1995;Cai et al, 2001). Moreover, since octopus cells emphasize transient stimulus features like gaps and onsets, known to be important in speech processing (e.g., Stevens, 1995) as well as in auditory binding (e.g., Bregman, 1990), it has been suggested that they are also involved in these auditory tasks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation